Design of Instrumented Shoes for Gait Characterization: A Usability Study With Healthy and Post-stroke Hemiplegic Individuals - Solanki, Dhaval; Lahiri, Uttama (Frontiers in Neuroscience, 2018)
Ambulation is a fundamental requirement of human beings for enjoying healthy community life. A neurological disorder such as stroke can significantly affect one’s gait thereby restricting one’s active community participation. To quantify one’s gait, spatiotemporal gait parameters are widely used in clinical context with different tests such as 10 meter walk test, 6 minute walk test, etc. Though these conventional observation-based methods are powerful, yet they often suffer from subjectivity, a scarcity of adequately trained therapists and frequent clinical visits for assessment. Researchers have been exploring the technology-assisted solutions for gait characterization. There are laboratory-based stereophotogrammetric methods and walk mats that are powerful tools as far as gait characterization is concerned. However, these suffer from issues with portability, accessibility due to high cost, labor-intensiveness, etc. Faced with these issues, our present research tries to investigate and quantify the gait abnormalities in individuals with neurological disorder by using a portable and cost-effective instrumented shoes (ShoesFSR henceforth). The in-house developed ShoesFSR comprised of a pair of shoes instrumented with Force Sensing Resistors (FSR) and a wireless data acquisition unit. The real-time FSR data was acquired wirelessly and analyzed by a central console to offer quantitative indices of one’s gait. Studies were conducted with 15 healthy participants and 9 post-stroke survivors. The spatiotemporal gait parameters of healthy participants measured using ShoesFSR were validated with standard methods such as stereophotogrammetric system and paper-based setup. Statistical analysis showed good agreement between the gait parameters measured using ShoesFSR and the standard methods. Specifically, the mean absolute error of the spatial parameters measured by the ShoesFSR, in the worst case, was 1.24% and that for the temporal parameters was 1.12% with that measured by standard methods for healthy gait. This research shows the potential of the ShoesFSR to quantify gait abnormality of post-stroke hemiplegic patients. In turn, the results show a promise for the future clinical use of the ShoesFSR.